The association of fluid balance with traumatic brain injury outcomes: A systematic review - Antonis Kalakoutas; Ashley Thomas; Thomas Fisher; Bethany Lane (Journal of Intensive Medicine)
Background: Fluid balance management is critical in moderate and severe traumatic brain injury (TBI) due to impaired cerebrovascular autoregulation. This study systematically reviews the association of fluid volume management with outcomes in moderate to severe TBI. Methods: We conducted a systematic literature search on MEDLINE, EMBASE, CINAHL, The Cochrane Database, and bibliographies of included articles. Studies assessing fluid volume management and outcomes in moderate/severe TBI patients were included. Risk of bias, publication bias, and heterogeneity were comprehensively assessed. Primary outcomes were short/long-term mortality and neurological outcomes. Secondary outcomes included the effect on intracranial pressure, development of acute kidney injury (AKI), refractory intracranial hypertension (RIH), pulmonary edema/acute respiratory distress syndrome, length of stay, and length of mechanical ventilation. Fluid balance groups were categorized into restrictive, euvolemic, and liberal. Results: Out of 2668 studies identified, 12 studies (seven observational and five randomized controlled trials [RCTs]) involving 9184 TBI patients were included. Euvolemic fluid balance was associated with lower odds of mortality compared to restrictive (odds ratio [OR] = 0.39, 95% confidence interval [CI]: 0.27 to 0.57, P <0.00001) and liberal groups (OR=0.47, 95% CI: 0.31 to 0.70, P=0.0003), and improved odds of favorable neurological outcomes compared to restrictive (OR=2.51, 95% CI: 1.72 to 3.66, P <0.00001) and liberal groups (OR=1.86, 95% CI: 1.18 to 2.92, P=0.007). Euvolemic balance also reduced the odds of AKI and RIH, and shortened the mean length of mechanical ventilation compared to liberal fluid balance groups but not the restrictive ones. Conclusions: Euvolemic fluid balance may improve key outcomes in TBI patients, including reduced mortality and better neurological outcomes. These findings underscore the need for RCTs to further assess euvolemic fluid management protocols in neurocritical care and their potential to inform clinical guidelines.